Complementary medicine use among general internal medicine inpatients in a Swiss university hospital. Issue 7 (19th May 2017) - Ducrest, Isabelle; Marques‐Vidal, Pedro; Faouzi, Mohamed; Burnand, Bernard; Waeber, Gérard; Rodondi, Pierre‐Yves
Summary: Background: Complementary Medicine (CM) is frequently used by the general population, but data about prevalence among hospitalised patients are scarce. We evaluated the prevalence and determinants of CM use by inpatients, lifetime, 2 months before and during their hospitalisation in a general internal medicine ward. Methods: Cross‐sectional survey conducted in September 2014 among adult (≥18 years) patients hospitalised for at least 1 day in the general internal medicine ward of the Lausanne University Hospital, Switzerland. The association between the socio‐demographic data and CM used were assessed using logistic regression model. Results: Among the 289 eligible patients, 130 (45%, mean age 68.9±16.4 years, 59.2% male) were included. The lifetime prevalence of CM use was 74.6%. One‐third (31.5%) and one‐tenth of patients reported CM use 2 months prior or during hospitalisation, respectively. The four most reported CM used during lifetime were homeopathy (54.6%), herbal medicine (49.5%), therapeutic massage (47.4%), and osteopathy (44.3%). Herbal medicine, homeopathy, meditation and therapeutic massage were the four main CM used during hospitalisation. On bivariate analysis, lifetime use of CM was significantly associated with higher level of education (apprenticeship: OR 3.2, 95% CI [1.20‐8.51], high school/university: OR 7.67, 95% CI [2.59‐22.70]; P =.004) and healthcare coverage for CM (OR 3.53, 95% CI [1.32‐9.46]; P =.014), but not with age and gender. During hospitalisation only 3.8% of patients were asked about CM use by physicians. Conclusion: One‐third of hospitalised patients used CM 2 months before hospitalisation and one‐tenth during hospital stay. CM use is seldom queried by hospital staff; better assessment of CM use among hospitalised patients could prevent potential adverse events or interactions.